Analysis of matrix metalloproteinases, especially MMP‐8, in gingival creviclular fluid, mouthrinse and saliva for monitoring periodontal diseases. Issue 1 (February 2016) - Sorsa, Timo; Gursoy, Ulvi K.; Nwhator, Solomon; Hernandez, Marcela; Tervahartiala, Taina; Leppilahti, Jussi; Gursoy, Mervi; Könönen, Eija; Emingil, Gulnur; Pussinen, Pirkko J.; Mäntylä, Päivi
Abstract: Matrix metalloproteinase‐8 is a promising candidate biomarker for oral fluid (gingival crevicular fluid, peri‐implant sulcular fluid and saliva) and mouthrinse chair‐side/point‐of‐care diagnostics to predict, diagnose and determine the progressive phases of episodic periodontitis and peri‐implantitis, as well as to monitor the treatments and medications. Matrix metalloproteinase‐8 can be used alone or together with interleukin‐1beta and Porphyromonas gingivalis to calculate cumulative risk score at the subject level as a successful diagnostic tool, especially in large‐scale public health surveys, in which a thorough periodontal examination is not feasible.